1864 Montana Acts 182 § 35 - (:unkn) unknown (General Publisher, 1864)
Prohibited dueling and killing a person with a rifle, shotgun, pistol, Bowie knife, dirk, small sword, backsword, or other dangerous weapon. Violators guilty of murder in the first degree.
--
Keywords: DUELING